2018
DOI: 10.1038/nrendo.2017.181
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin in the brain: from embryonic development to age-related decline in cognition

Abstract: A remarkable, totally unexpected aspect of the bone-derived hormone osteocalcin is that it is necessary for both brain development and brain function in the mouse since its absence results in a profound deficit in spatial learning and memory and an exacerbation of anxiety-like behavior. The regulation of cognitive function by osteocalcin, together with the fact its circulating levels decrease in midlife compared to adolescence in all species tested raised the prospect that osteocalcin may be an anti-geronic ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 87 publications
3
85
1
4
Order By: Relevance
“…RUNX2 gene encodes a transcription factor that regulates the expression of osteocalcin (16). Interestingly, low osteocalcin level is associated with age-related decline in cognitive function, which may contribute to the association between this RUNX2 variant and RBA (17,18). NKX6-2 encodes a transcription factor that regulates myelin sheath formation and maintenance in the central nervous system (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 gene encodes a transcription factor that regulates the expression of osteocalcin (16). Interestingly, low osteocalcin level is associated with age-related decline in cognitive function, which may contribute to the association between this RUNX2 variant and RBA (17,18). NKX6-2 encodes a transcription factor that regulates myelin sheath formation and maintenance in the central nervous system (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Other observed endocrine roles for OCN include influencing fetal brain development and adult animal behavior [8], and promoting adaptation of myofibers to exercise and maintaining muscle mass with ageing [9,10]. Cumulatively, the reports outlined above with the Osc -/Oscmice and, subsequently, a conditional knockout strain (Ocn-flox) made by the same investigative team [7] coupled with associated work [11][12][13][14][15][16][17][18] from this team, suggest that therapies which increase uncarboxylated osteocalcin levels may improve glucose intolerance, increase beta islet cell number, reduce insulin resistance, increase testosterone, improve male fertility, enhance muscle mass, and reduce declines in cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing clinical evidence indicated that patients with PD have a higher susceptibility to another very common age-related disease–osteoporosis (Torsney et al, 2014 ). The cross-talk between bone and brain was suggested by a series of works from Karsenty’s group revealing that bone-derived osteocalcin (OCN) is important for brain development (Obri et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%